Recommendations on treatment of nail and fingertip injuries in children. Cases series and literature review (2016)
Introduction: Nail and fingertip injuries in children are very frequent and may range from a simple nail or fingertip injury to amputations.Objective: To present a series of cases with their clinical and demographic characteristics and to describe the current concepts for the treatment of these injuries.Materials and methods: A series of cases presenting fingertip injuries was analyzed for six months. Epidemiology of injuries is described and the current concepts of their treatment are reviewed.Results: 60% of the injuries analyzed in this study occurred in male subjects; 88% of patients suffered crush injuries, the nail was affected in 98% of the cases, sterile matrix damage was observed in 64% and germinal matrix damage was experienced in 34% of the cases. The soft tissue around the finger was affected in 40% of the cases and associated fractures were observed in 55% of the cases.Conclusion: Fingertip crush caused by closing doors was the most frequent injury, which implied a higher involvement of the nail. An adequate treatment focused on the anatomic repair of the nail bed, the relocation of the nail plate and, in some cases, the use of flaps to cover defects in the soft tissue is ideal for this type of injuries, and must be provided as fast as possible to avoid secondary deformities.